Role of Heart Type Fatty Acid Binding Protein (HFabp) As Cardiac Bio Marker in Ischemic Heart Disease - Baig, Imran Mehboob; ., Arjumand; Memon, Abdul Shakoor; Asadullah, M. (International Journal of Pathology, 2018)
Introduction: Cardiovascular diseases constitute significant morbidity and mortality worldwide. Heart-typefatty acid binding protein (H-FABP) is a small intracellular protein which is abundant in the myocardium andrapidly released within 1-3 hours from damaged cardiomyocytes and may be the earliest available plasma markerof acute myocardial injury.Material and Method: A cross sectional study was conducted at the department of physiology, BMSI, JPMCfrom 2010 to 2012. During this period 60 patients suspected with Ischemic heart disease were included, out ofwhich 37 were male and 23 were female. Levels of cardiac markers troponin T and H-FABP were measured in theserum of all patients and the results were compared.Result: Total numbers of 60 individuals were included in study out of which 61.66% (37) were males and 38.33%were females. H-FABP shows a positive result within one hour of onset of symptoms with a mean value of 22.8ng/ml while Troponin T shows a negative result with a mean value of 0.28 ng/ml. While after 1 hour of onset ofsymptoms both H-FABP and Troponin T are showing positive results by having a value >6 ng/ml and >1.5ng/ml respectively.Conclusion: Point-of-care assays of H-FABP in patients presenting within one hours of symptom onset may leadto an earlier diagnosis of Ischemic Heart Disease.